ENGAGING PRE SERVICE TEACHERS IN MULTIMODAL READING WITH LEARNING LOGS: AN ACTION CLASSROOM-BASED RESEARCH - Elih Sutisna Yanto; Kusrin Kusrin (Jurnal Penelitian Humaniora, 2020)
Students’ reading comprehension on disciplinary texts commonly involves the interaction between the cognitive aspect and the text itself, but little is known how it is carried out through multimodal reading. To fill this practical void, this article reports the findings of classroom action research of the pre-service teachers learning disciplinary vocabularies through different modes of meaning, the socially and culturally shaped resources or semiotic structure for making meaning: video viewing and graphic organizers. This study proposes that multimodal reading has the potential to promote the role of student teachers as designers and navigators in reading English disciplinary texts. Pedagogically, this multimodal engagement not only creates interactive content learning but also it encourages the students to become autonomous language learners. In addition to multimodal reading activities, the students were motivated not only to learn about language but also to learn through language. Moreover, multimodality reading tasks can scaffold comprehension and production of the academic language of the students. Finally, students who are engaged in cognitive work in content areas (e.g., statistics for second language research) have the motivation to learn a language that supports their learning. Multimodality reading tasks can support students ‘communication, increasing students’ academic writing and students’ academic vocabulary development as well.